Exploring the associations between elevated plasma SP-D levels and OSCAR gene expression as potential biomarkers in patients with COPD: a cross-sectional study - Mukhtar, Saima; Choudhry, Nakhshab; Saeed, Saqib; Hanif, Asif; Gondal, Aamir J.; Yasmin, Nighat (Frontiers in Pharmacology, 2024)
Chronic Obstructive Pulmonary Disease (COPD) imposes a substantial burden on patients and health care systems. Spirometry is the most widely used test to diagnose the disease, however, a surrogate marker is required to predict the disease pattern and progression.The aim of the current study was to explore the association of elevated levels of plasma surfactant protein D (SP-D) with gene expression of osteoclast associated receptor (OSCAR) and lung functions as potential diagnostic biomarkers of COPD.This cross-sectional study employed convenience sampling. As men make up majority of patients in Outpatient Department and smoking being common among Pakistani men, choosing males offered a representative sample.. Using a post bronchodilator forced expiratory volume in first second (FEV1) to forced vital capacity (FVC) of less than 0.70 (FEV1/FVC < 0.7), COPD patients were diagnosed on spirometry (n=41). Controls were healthy individuals with FEV1/FVC > 0.7 (n=41). Plasma SP-D levels were measured using enzyme linked immunosorbent assay (ELISA). Commented [u1]: Comment 2 for Reviewer 2: Word "diagnostic" added. Commented [u2]: Comment 4 for Reviewer 2 Explained the reason for enrolling males only.Gene expression of OSCAR was determined by (real time polymerase chain reaction (qPCR) and subsequently analyzed by (threshold cycle) Ct method.. Statistical Package for Social Sciences (SPSS) version 20 was used for statistical analysis.Mean BMI of controls 25.66±4.17 kg/m 2 was higher than that of cases 23.49±2.94 kg/m 2 (p=.008). Median age of controls was 49 interquartile range (IQR) 42.0-65.0 years and of cases was 65 years ). SP-D concentration was non significantly higher in COPD patients [4.96 ng/mL (IQR 3.26-7.96)] as compared to 3.64 ng/mL (IQR 2.60-8.59) in controls (p=.209). Forced expiratory ratio (FEV1/FVC), FEV1was related to gene expression of OSCAR (p=<.001). Gene expression of OSCAR was significantly related to SP-D (p=.034). Multiple regression model found FEV1 and FVC to have significant effect on gene expression of OSCAR (p-values <0.001, 0.001 respectively)..Gene expression of OSCAR was increased in COPD patients and related directly to SP-D levels and inversely to lung functions in cohort of this study, suggesting that OSCAR along with SP-D may serve as a diagnostic biomarker of COPD.